Conductive porous substrate, gas diffusion electrode substrate, electrochemical device, and vehicle

CN122953545APending Publication Date: 2026-10-20TORAY INDUSTRIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580020723.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-19
Filing Date
2025-03-25
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

并且,如果最终气体扩散电极基材的全部细孔被堵塞,则导致发电停止即所谓的水淹(flooding)现象

Benefits of technology

[0030]根据本发明,能够提供不含氟而具有高的疏水性的导电性多孔基材。所得到的导电性多孔基材能够适用于气体扩散电极基材和燃料电池等电化学装置。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The objective of this invention is to provide a fluorine-free conductive porous substrate with high hydrophobicity. This invention relates to a conductive porous substrate comprising carbon fibers, on which a resin comprising nano-carbon aggregates is supported. The conductive porous substrate has a slip angle of 2° or more and 60° or less, and the mass ratio of fluorine content to carbon content (F / C) is 0.01 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive porous substrate suitable for use in electrochemical devices such as fuel cells, particularly suitable for solid polymer fuel cells, a gas diffusion electrode substrate having a porous layer on the conductive porous substrate, an electrochemical device having the gas diffusion electrode substrate, and a vehicle using the electrochemical device. Background Technology

[0002] Solid polymer fuel cells are highly energy efficient, with water as their only emission, making them a promising candidate for widespread adoption as a clean energy source. One of the most anticipated applications of solid polymer fuel cells is as a power source for vehicles such as automobiles.

[0003] The basic components of a solid polymer fuel cell are a polymer electrolyte membrane, catalyst layers formed on both sides of the polymer electrolyte membrane, a gas diffusion electrode substrate formed on the outside of the catalyst layers, and a separator sandwiching them.

[0004] A fuel cell is a system that electrically extracts the energy generated when hydrogen and oxygen react to produce water. Therefore, if the electrical load increases, the current drawn from the cell increases, resulting in the production of a large amount of water (water vapor). If this water vapor condenses into droplets upon cooling, clogging the pores of the gas diffusion electrode substrate, the supply of gas (oxygen and / or hydrogen) to the catalyst layer decreases. Furthermore, if all the pores of the gas diffusion electrode substrate eventually become blocked, power generation ceases, a phenomenon known as flooding. Traditionally, gas diffusion electrode materials used in fuel cells have been required to have high drainage performance to effectively suppress flooding.

[0005] To achieve high drainage performance, gas diffusion electrode substrates sometimes employ a morphology where a porous layer called an MPL (Micro Porous Layer) is formed on one side of a hydrophobic conductive porous substrate. To impart hydrophobicity to the conductive porous substrate, combinations with carbon materials have been investigated in addition to adding highly hydrophobic fluoropolymers. For example, Patent Document 1 discloses a gas diffusion electrode substrate for fuel cells, in which a microporous layer composed of carbon-based fillers and fluoropolymers is formed on one side of the electrode substrate. The water slip angle on the side opposite to the surface where the microporous layer is formed is less than 30 degrees, and the vertical gas permeation resistance is 15~190 mmAq.

[0006] Prior art literature

[0007] Patent Document 1: International Publication No. 2015 / 125750 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] In conductive porous substrates used for gas diffusion electrode substrates requiring high hydrophobicity, hydrophobic agents containing organofluorine compounds, known as PFAS (per- and polyfluorinated alkyl substances), are employed. However, fluorine compounds are considered perpetual chemicals, exhibiting low biodegradability and raising concerns about their potential environmental and human health impacts. PFAS comprise over 4730 organofluorine compounds, and the effects of various compounds on human health and the environment require further scientific verification. From a preventative perspective, there is a need for conductive porous substrates with high hydrophobicity that do not utilize PFAS.

[0010] While Patent Document 1 achieves high hydrophobicity, its effect is limited to the use of fluorine compounds, and it does not study conductive porous substrates that do not use fluorine compounds.

[0011] Furthermore, the inventors conducted in-depth research and found that it is difficult to impart sufficient hydrophobicity to conductive porous substrates simply by using hydrophobic agents that do not use fluorine.

[0012] Therefore, the object of the present invention is to provide a fluorine-free, highly hydrophobic, conductive porous substrate, and thereby to provide an electrochemical device capable of stable power generation.

[0013] Methods for solving problems

[0014] The present invention and its preferred embodiments have the following structure.

[0015] (1) A conductive porous substrate comprising carbon fibers, wherein a resin comprising nano-carbon aggregates is supported on the carbon fibers, wherein the conductive porous substrate has a slip angle of 2° or more and 60° or less, and the mass ratio of fluorine content to carbon content F / C is 0.01 or less.

[0016] (2) The conductive porous substrate according to (1) further comprises a hydrophobic agent.

[0017] (3) According to the conductive porous substrate described in (1) or (2), the primary particles of the nano-carbon aggregate are spherical.

[0018] (4) The conductive porous substrate according to any one of (1) to (3) has a primary particle size of 10 nm or more and 200 nm or less.

[0019] (5) The conductive porous substrate according to any one of (1) to (4) is composed of carbon black.

[0020] (6) According to the conductive porous substrate described in (1) or (2), the nano-carbon aggregate is a fibrous nano-carbon aggregate with a diameter of 5 nm or more and 200 nm or less.

[0021] (7) The conductive porous substrate according to any one of (1) to (6) has a proportion of the nano-carbon aggregate in 100% by mass of the conductive porous substrate of 0.5% by mass or more and 16.0% by mass or less.

[0022] (8) According to the conductive porous substrate of (2), the hydrophobic agent has a non-fluorinated alkyl group.

[0023] (9) According to the conductive porous substrate of (8), the number of carbon atoms constituting the non-fluorinated alkyl group is 8 or more and 40 or less.

[0024] (10) When the conductive porous substrate described in (2) is heat-treated at 400°C for 1 hour in an atmospheric atmosphere, the slip angle increases by more than 10° or the hydrophobicity is lost.

[0025] (11) A gas diffusion electrode substrate having a porous layer containing carbonaceous particles and binder resin on one side of a conductive porous substrate as described in any one of (1) to (10).

[0026] (12) According to the gas diffusion electrode substrate of (11), the mass ratio of fluorine content to carbon content in the porous layer, F / C, is less than 0.01.

[0027] (13) An electrochemical device having a conductive porous substrate as described in any one of (1) to (10) or a gas diffusion electrode substrate as described in (11).

[0028] (14) A means of transportation that uses the electrochemical device described in (13) as a power source.

[0029] The effects of the invention

[0030] According to the present invention, a conductive porous substrate with high hydrophobicity and free of fluorine can be provided. The resulting conductive porous substrate is suitable for use in electrochemical devices such as gas diffusion electrode substrates and fuel cells. Detailed Implementation

[0031] The embodiments of the present invention will be described in detail.

[0032] <Conductive Porous Substrate>

[0033] The conductive porous substrate of the present invention comprises carbon fiber.

[0034] Examples of carbon fibers include polyacrylonitrile (PAN) based, pitch-based, and rayon-based fibers. Among these, PAN-based and pitch-based carbon fibers are preferred due to their superior mechanical strength.

[0035] The carbon fiber preferably has an average fiber diameter of 3 μm or more and 20 μm or less. By making the average fiber diameter 3 μm or more, more preferably 5 μm or more, the pore size of the conductive porous substrate can be increased, improving drainage performance when used in fuel cells and more effectively suppressing flooding. On the other hand, by making the average diameter 20 μm or less, more preferably 12 μm or less, and even more preferably 10 μm or less, water vapor diffusivity can be reduced, and the power generation performance at high temperatures when used in fuel cells can be more effectively improved.

[0036] Furthermore, it is preferable to use two or more types of carbon fibers with different average diameters. This improves the surface smoothness of the conductive porous substrate.

[0037] The average fiber diameter of carbon fiber can be calculated as follows: The carbon fiber is photographed at a magnification of 1000x or higher using a microscope such as a scanning electron microscope. Thirty different individual fibers are randomly selected, their diameters are measured, and the average value is calculated. For example, a scanning electron microscope such as the Hitachi S-5500 or an equivalent product manufactured by Hitachi, Ltd. can be used.

[0038] The average length of the carbon fiber is preferably 3 mm or more and 20 mm or less. By making the average length 3 mm or more, more preferably 5 mm or more, the electrode substrate exhibits excellent mechanical strength, electrical conductivity, and thermal conductivity. On the other hand, by making the average length 20 mm or less, more preferably 15 mm or less, the dispersion of the carbon fiber during the fabrication of the carbon fiber paper body can be improved, resulting in a uniform electrode substrate. The carbon fiber can be obtained by methods such as cutting continuous carbon fibers to the desired length.

[0039] The average length of carbon fiber can be calculated as follows: The carbon fiber is photographed using a microscope such as a scanning electron microscope at a magnification of 50x or higher. Thirty different individual fibers are randomly selected, their lengths are measured, and the average length is calculated. For example, a scanning electron microscope such as the Hitachi S-5500 or an equivalent product manufactured by Hitachi, Ltd. can be used.

[0040] The average fiber diameter or average length of carbon fiber can be determined or calculated by directly observing the carbon fiber used as the raw material for the conductive porous substrate, or by observing the conductive porous substrate.

[0041] Examples of the carbon fibers used in the conductive porous substrate include carbon fiber fabric, carbon fiber paper, carbon fiber nonwoven fabric, carbon felt, carbon paper, and carbon cloth. Among these, carbon paper, a substrate containing carbides obtained by bonding carbon fiber paper with carbides, is preferred because it exhibits excellent "elasticity" in absorbing dimensional changes in the thickness direction of the electrolyte membrane when used in fuel cells. Hereinafter, the substrate composed of the carbon fibers will also be referred to as "carbon fiber substrate".

[0042] In the conductive porous substrate, a resin containing nano-carbon aggregates is supported on the carbon fibers. Here, "supported" refers to a state where the resin containing nano-carbon aggregates is supported on the carbon fibers and immobilized. Furthermore, whether it is in an immobilized state can be determined by performing three operations of immersing the conductive porous substrate in water and then removing it, and by observing whether more than 30% by mass of the supported nano-carbon aggregates remain attached to the carbon fiber substrate without detaching.

[0043] The nano-carbon aggregates, by imparting irregularities to the surface of the conductive porous substrate, enhance the effect of the hydrophobic agent described later, while simultaneously increasing the amount of hydrophobic agent adhered. The nano-carbon aggregates do not need to be in an aggregated form before being loaded onto the carbon fiber substrate; however, from an operational point of view, it is preferable to aggregate before loading.

[0044] Examples of nano-carbon constituting the nano-carbon aggregates include carbon black or fibrous nano-carbon.

[0045] From the viewpoint of obtaining a high-purity substance, carbon black is preferred. Examples of carbon black include acetylene black, Ketjen black, and furnace black. Among these, acetylene black is preferred from the viewpoint of having fewer impurities such as iron that would reduce power generation performance when used in fuel cells.

[0046] Carbon nanotubes are preferred as the fibrous carbon nanotubes.

[0047] From the viewpoint of facilitating gas diffusion when used in fuel cells, the primary particles of the nano-carbon are preferably spherical.

[0048] When the primary particles of the nano-carbon are spherical, the particle size of the primary particles is preferably 10 nm or more and 200 nm or less. By making the particle size of the primary particles 10 nm or more, the operability can be improved. On the other hand, by making the particle size of the primary particles 200 nm or less, the conductive porous substrate can be given more unevenness with a smaller amount of addition, thereby increasing the specific surface area.

[0049] The particle size of primary carbon nanoparticles can be determined and calculated using a scanning electron microscope (such as the S-5500 manufactured by Hitachi, Ltd.) or a transmission electron microscope at a magnification of 200,000x or higher. Specifically, 100 primary particles constituting a carbon nanoparticle aggregate are randomly observed, and their particle sizes are measured. The average value of the obtained particle sizes is calculated as the particle size of the primary particle. The particle size of each primary particle is calculated from the average of the smallest circumscribed circle diameter and the largest inscribed circle diameter. Since a carbon nanoparticle aggregate is composed of multiple primary particles, there may be cases where the boundary lines of each primary particle are unclear. In such cases, the constricted necks where the primary particles meet are assumed to be the boundary lines, and the particle size of each primary particle is measured.

[0050] The diameter of the fibrous carbon nanoparticles is preferably 5 nm or more and 200 nm or less. By making the diameter less than 200 nm, the conductive porous substrate can be given more unevenness with a smaller amount of the carbon nanoparticle aggregate, thereby increasing the specific surface area. On the other hand, by making the diameter more than 5 nm, the fibrous carbon nanoparticles can be prevented from entangled with each other, thereby making it easier to form unevenness on the conductive porous substrate.

[0051] The diameter of fibrous carbon nanotubes can be measured and calculated using a scanning electron microscope (such as the S-5500 manufactured by Hitachi, Ltd.). Specifically, a conductive porous substrate is magnified more than 100,000 times and photographed. One hundred different fibrous carbon nanotubes are randomly selected and their diameters are measured. The average diameter of each fibrous carbon nanotube is calculated as its diameter. The diameter of each fibrous carbon nanotube can be calculated from the average of the smallest circumscribed circle diameter and the largest inscribed circle diameter based on the observed cross-section, or the width (thickness) of the fiber when observed from above can be used as the diameter.

[0052] The diameter of the carbon nanoparticle aggregate is preferably 10 μm or less. The diameter of the carbon nanoparticle aggregate can be determined by observation using a scanning electron microscope at a magnification of 5000x or higher. Specifically, 100 carbon nanoparticle aggregates are randomly observed, and the diameter of the circumscribed sphere is measured and taken as the diameter of the carbon nanoparticle aggregate. A scanning electron microscope (e.g., the S-5500 manufactured by Hitachi, Ltd.) can be used as the microscope capable of performing such observation.

[0053] The content of the nano-carbon aggregate in 100% by mass of the conductive porous substrate is preferably 0.5% by mass or more and 16.0% by mass or less. By making the proportion of the nano-carbon aggregate 0.5% by mass or more, more effective unevenness can be formed while improving the hydrophobicity of the conductive porous substrate. On the other hand, by making the proportion of the nano-carbon aggregate 16.0% by mass or less, the obstruction of the nano-carbon aggregate to gas diffusion inside the conductive porous substrate can be suppressed.

[0054] The resin is an amorphous organic compound that functions to bond the nano-carbon aggregates to the carbon fiber substrate. Examples of resins capable of bonding the nano-carbon aggregates to the carbon fiber substrate include polyester resins, polyethylene, polypropylene, polystyrene, acrylic resins, ABS resins, polyvinyl chloride, nylon, polyacetal, polycarbonate, polybutylene terephthalate, polyarylates, phenolic resins, epoxy resins, polyurethane resins, melamine resins, and unsaturated polyester resins. From the viewpoint of excellent heat resistance and ease of obtaining an aqueous dispersion, polyester resins are preferred.

[0055] The conductive porous substrate preferably further comprises a hydrophobic agent. In this invention, a hydrophobic agent refers to one that, by being contained in the conductive porous substrate, reduces the slip angle of the conductive porous substrate by more than 10° (described later).

[0056] The hydrophobic agent preferably has a non-fluorinated alkyl group. A non-fluorinated alkyl group refers to an alkyl group that does not contain fluorine atoms. By having a non-fluorinated alkyl group, it is possible to avoid the presence of PFAS, which may have adverse effects on human health and the environment, and to impart high hydrophobicity to conductive porous substrates.

[0057] The number of carbon atoms constituting the nonfluorinated alkyl group is preferably 8 or more and 40 or less, more preferably 12 or more and 30 or less.

[0058] The presence of non-fluorinated alkyl groups in hydrophobic agents adhering to conductive porous substrates can be confirmed in the following order.

[0059] (i) The conductive porous substrate cut into 1-2 cm squares is immersed in hexane and heated to 50°C while being irradiated with ultrasound to extract the soluble substances.

[0060] (ii) Measure the IR or 1H NMR of the soluble substances extracted in (i).

[0061] (iii) Confirm the presence of peaks or absorption lines of CH3- and -CH2- from non-fluorinated alkyl groups. In the case of IR, confirm the presence or absence of peaks or absorption lines at 2800–3000 cm⁻¹ from CH3 or CH2 stretching vibrations. -1The peaks generated at the point were confirmed by 1H NMR, with absorption lines observed in the range of 0.95–0.85 from CH3- and in the range of 1.35–1.20 from -CH2-.

[0062] The number of carbon atoms of the non-fluorinated alkyl group in a hydrophobic agent attached to a conductive porous substrate can be identified in the following order.

[0063] (i) The conductive porous substrate cut into 1-2 cm squares is immersed in hexane and heated to 50°C while being irradiated with ultrasound to extract the soluble substances.

[0064] (ii) Use GC / MS to calculate the number of carbon atoms in the soluble material extracted in (i).

[0065] The hydrophobic agent is preferably composed of an organic compound and does not contain fluorine atoms. This can be confirmed by measuring the drop angle after heat-treating the conductive porous substrate at 400°C for 1 hour in an atmospheric atmosphere. This is because hydrophobic agents without fluorine atoms are mostly different from fluorine-containing resins, i.e., so-called fluororesins, and heat treatment at 400°C for 1 hour significantly impairs their hydrophobicity. Specifically, when the conductive porous substrate containing the hydrophobic agent without fluorine atoms is heat-treated at 400°C for 1 hour in an atmospheric atmosphere, the drop angle (described later) increases by more than 10° compared to before the heat treatment, or the water droplets are absorbed into the conductive porous substrate when a drop of purified water is placed on it due to loss of hydrophobicity, making it impossible to measure the drop angle. In other words, the conductive porous substrate of the present invention preferably exhibits a drop angle increase of more than 10° or loses its hydrophobicity when heat-treated at 400°C for 1 hour in an atmospheric atmosphere.

[0066] Examples of fluorine-free hydrophobic agents include hydrocarbon-based ones such as XF-5003, XF-5005, XF-5007 (manufactured by Daikin Industries, Ltd.), Racguard NOF (manufactured by Rakuto Chemical Industries, Ltd.), "Modiper" FP100 (manufactured by Nippon Yuko Co., Ltd.), Richenparan PG-70 (manufactured by Riken Kogyo Co., Ltd.), "Meishield" Z-1, and "Meishield" Z-210 (manufactured by Meisei Chemical Co., Ltd.). Examples of silicone-based hydrophobic agents include Richenparan SG-54 (manufactured by Riken Kogyo Co., Ltd.), "Neoseed" NR7080, and "Neoseed" NR8800 (manufactured by Nichika Chemical Co., Ltd.). In addition, examples of paraffin-based hydrophobic agents include SDX-5100 (trade name) (manufactured by Sumitomo Chemical Chemtex Co., Ltd.) and Paradit ZS (manufactured by Meisei Chemical Industry Co., Ltd.).

[0067] The resin and the hydrophobic agent may contain the same material. In this case, the same material serves both to improve hydrophobicity and to fix the nano-carbon aggregates.

[0068] The fluorine content to carbon content mass ratio (F / C) in the conductive porous substrate is 0.01 or less. Here, "F / C mass ratio of 0.01 or less" means that the conductive porous substrate is substantially fluorine-free. By ensuring that the conductive porous substrate is substantially fluorine-free, not only is the possibility of unintentional release of fluorine compounds into the environment reduced, but the management costs required to prevent the release of fluorine compounds into the environment from production to disposal are also reduced.

[0069] The mass ratio F / C of the conductive porous substrate can be determined and calculated in the following order.

[0070] (i) The surface of the conductive porous substrate was observed by scanning electron microscopy (SEM) at a magnification of 2000x.

[0071] (ii) Using energy dispersive X-ray analysis (EDX), an electron beam was irradiated onto the magnified observation area in (i) at an accelerating voltage of 20 kV, and the reflected characteristic X-rays were detected.

[0072] (iii) By quantifying the characteristic X-rays detected in (ii), the mass fractions of fluorine and carbon are derived, and the ratio of the mass fraction of fluorine to the mass fraction of carbon is calculated.

[0073] (iv) Randomly perform the above (i) to (iii) measurements and calculations 10 times in different fields of view. Among the 10 ratios calculated, remove the two largest and two smallest values, a total of 4 values, and calculate the average of the remaining 6 values ​​as the mass ratio F / C.

[0074] When the conductive porous substrate is used in a fuel cell, its thickness is preferably 70 μm or more and 220 μm or less. By making the thickness 220 μm or less, more preferably 150 μm or less, and even more preferably 120 μm or less, gas diffusivity can be improved. On the other hand, by making the thickness 70 μm or more, mechanical strength can be maintained, making processing in the manufacturing process easier.

[0075] The slip angle of the conductive porous substrate is 2° or more and 60° or less. By making the slip angle 60° or less, more preferably 40° or less, and even more preferably 30° or less, water flooding during use in fuel cells can be suppressed. In addition, by making the slip angle 40° or less, more preferably 30° or less, water flooding can be suppressed even under higher humidity conditions. On the other hand, by making the slip angle 2° or more, it is possible to prevent the conductive porous substrate from becoming a water-impermeable wall due to excessive increase in hydrophobicity, thus maintaining the water drainage function.

[0076] The slip angle can be calculated as follows: Place a 10 μL droplet of purified water on a horizontally placed, stationary conductive porous substrate, and calculate the average angle at which the droplet begins to roll when the conductive porous substrate is tilted at a speed of 1° / second at 10 sample points. The slip angle can be measured using an automatic contact angle meter (e.g., Kyowa Interface Science Co., Ltd. DM-501 or equivalent). Alternatively, as described later, if the conductive porous substrate has a porous layer on one side, the slip angle can be calculated for the side without the porous layer.

[0077] In the gas diffusion electrode substrate described later, whether it contains a fluorine-free hydrophobic agent can be confirmed by measuring the slip angle on the exposed side of the conductive porous substrate where the porous layer has not been formed after heat-treating the gas diffusion electrode substrate at 400°C for 1 hour in an atmospheric atmosphere.

[0078] <Gas Diffusion Electrode Substrate>

[0079] The gas diffusion electrode substrate of the present invention has a porous layer containing carbonaceous particles and binder resin on one side of the conductive porous substrate.

[0080] As the carbonaceous particles, those with a large specific surface area are preferred to facilitate the formation of a porous structure. Specifically, carbon black is preferred, and more specifically, acetylene black, Ketjen black, furnace black, etc. are preferred. Among these, acetylene black is more preferred from the viewpoint of having fewer impurities such as iron that would reduce power generation performance when used in fuel cells.

[0081] Examples of adhesive resins capable of retaining the carbonaceous particles on the conductive porous substrate include polyester resins, polyethylene, polypropylene, polystyrene, acrylic resins, ABS resins, polyvinyl chloride, nylon, polyacetal, polycarbonate, polybutylene terephthalate, polyarylate, phenolic resins, epoxy resins, polyurethane resins, melamine resins, and unsaturated polyester resins. Among these, polyester resins are more preferred from the viewpoint of excellent heat resistance and ease of obtaining aqueous dispersions.

[0082] The adhesive resin may be the same material as the resin containing the nano-carbon aggregates in the conductive porous substrate.

[0083] From the viewpoint of further improving hydrophobicity, the porous layer preferably contains a fluorine-free hydrophobic agent. In particular, when the gas diffusion electrode substrate is used in a fuel cell, the porous layer readily improves gas diffusivity in the direction perpendicular to the high surface for diffusing gas supplied from the membrane to the catalyst, drainage for discharging liquid water generated during the electrochemical reaction to the membrane, and conductivity for extracting the generated current; therefore, it is preferred. Furthermore, the porous layer also promotes the reverse diffusion of moisture to the electrolyte membrane and wets the electrolyte membrane in the fuel cell; therefore, it is preferred.

[0084] The adhesive resin and the fluorine-free hydrophobic agent contained in the porous layer can be the same material. In this case, the material serves two purposes: enhancing the hydrophobicity of the hydrophobic agent and retaining the carbonaceous particles.

[0085] The fluorine content to carbon content in the porous layer is preferably a fluorine / C mass ratio of 0.01 or less. Here, "a mass ratio of 0.01 or less" means that the porous layer is substantially free of fluorine. By ensuring that the porous layer is substantially free of fluorine, not only can the possibility of unintentional emission of fluorine compounds into the environment be reduced, but also the management costs required to prevent the emission of fluorine compounds into the environment from production to disposal can be reduced.

[0086] The mass ratio F / C can be determined and calculated in the following order.

[0087] (i) The surface of the porous layer was observed at 2000x magnification using a scanning electron microscope (SEM).

[0088] (ii) Using energy dispersive X-ray analysis (EDX), an electron beam was irradiated onto the magnified observation area in (i) at an accelerating voltage of 20 kV, and the reflected characteristic X-rays were detected.

[0089] (iii) By quantifying the characteristic X-rays detected in (ii), the mass fractions of fluorine and carbon are derived, and the ratio of the mass fraction of fluorine to the mass fraction of carbon is calculated.

[0090] (iv) Randomly perform the above (i) to (iii) measurements and calculations 10 times in different fields of view. Among the 10 ratios calculated, remove the two largest and two smallest values, a total of 4 values, and calculate the average of the remaining 6 values ​​as the mass ratio F / C.

[0091] <Method for Manufacturing Conductive Porous Substrates>

[0092] An example of a method for manufacturing the conductive porous substrate of the present invention will be described. However, the following description should not be construed as limiting the conductive porous substrate of the present invention.

[0093] (Resin loading process)

[0094] The process of loading a resin containing nano-carbon aggregates onto a carbon fiber substrate is also called a "resin loading process". Examples of methods in the resin loading process include immersing the carbon fiber substrate in a liquid composition formed by dispersing the resin containing the nano-carbon aggregates in a solvent, coating the liquid composition onto the carbon fiber substrate, and spraying the liquid composition onto the carbon fiber substrate using a sprayer.

[0095] The hydrophobicity of the conductive porous substrate can be controlled by adjusting the amount of hydrophobic agent applied in the hydrophobic agent application process (described later), or by adjusting the loading amount of the resin containing the nano-carbon aggregates in the resin loading process. If the loading amount of the nano-carbon aggregates increases, the surface area of ​​the conductive porous substrate increases, thus increasing the amount of hydrophobic agent applied, resulting in improved hydrophobicity.

[0096] One method for preparing the liquid composition is to disperse the nano-carbon or the nano-carbon aggregate together with the resin in a solvent. In this method, a dispersant may be further added to the solvent. From the viewpoint of preventing unwanted ions from remaining in the conductive porous substrate, a nonionic dispersant is preferred.

[0097] (Heating process)

[0098] If the dispersant remains on the conductive porous substrate, it may reduce the hydrophobicity. Therefore, it is preferable to heat the substrate at a temperature above 200°C after the nano-carbon aggregates have adhered to the surface of the carbon fiber substrate. This process is also called the "heating process." Through this heating process, the dispersant can be burned off.

[0099] (Hydrophobic agent adhesion process)

[0100] Preferably, the hydrophobic agent is applied after the resin loading step or the heating step. This step is also called the "hydrophobic agent application step". By applying an appropriate amount of hydrophobic agent in the hydrophobic agent application step, it is easy to make the slip angle of the conductive porous substrate 2° or more and 60° or less. As a method for applying the hydrophobic agent, for example, there is a method of immersing the conductive porous substrate after the resin loading step or the heating step in a dispersion of the hydrophobic agent and then drying it, or a method of coating the conductive porous substrate after the resin loading step or the heating step with a dispersion of the hydrophobic agent and then drying it.

[0101] <Method for Manufacturing Gas Diffusion Electrode Substrate>

[0102] An example of a method for manufacturing the gas diffusion electrode substrate of the present invention will be described. However, the following description does not limit the manner in which the gas diffusion electrode substrate of the present invention is manufactured.

[0103] (Porous layer formation process)

[0104] By forming the porous layer containing the carbonaceous particles and the binder resin on one side of the conductive porous substrate, the gas diffusion electrode substrate of the present invention can be obtained. This process is also referred to as the porous layer formation process.

[0105] As a method in the process of forming the porous layer, examples include coating a dispersion of the carbonaceous particles and the binder resin onto the conductive porous substrate and then drying and firing it. Water is preferred as the dispersion medium for ease of handling. In this case, a dispersant can be used to uniformly disperse the carbonaceous particles in the water, which is the dispersion medium. From the viewpoint of preventing unwanted ions from remaining in the porous layer, a nonionic dispersant is preferred.

[0106] (Porous layer heating process)

[0107] If the dispersant remains in the porous layer during the porous layer formation process, it may reduce the hydrophobicity of the porous layer. Therefore, it is preferable to heat the porous layer at 200°C or higher under atmospheric conditions after the porous layer formation process to burn off the dispersant. This process is also called the "porous layer heating process".

[0108] (Hydrophobic agent adhesion process)

[0109] From the perspective of further improving hydrophobicity, it is preferable to attach a fluorine-free hydrophobic agent to the porous layer. This process is also known as the "hydrophobic agent attachment process".

[0110] As a method of imparting the hydrophobic agent, there are methods such as immersing the gas diffusion electrode substrate in a dispersion of the hydrophobic agent and then drying it, or coating the surface of the porous layer or the surface of the porous layer and the conductive porous substrate with a dispersion of the hydrophobic agent and then drying it.

[0111] <Electrochemical Device>

[0112] The electrochemical device of the present invention comprises the conductive porous substrate of the present invention or the gas diffusion electrode substrate of the present invention. Examples of such electrochemical devices include fuel cells, water electrolysis devices, CO2 electrolysis devices, and various storage batteries. The conductive porous substrate and the gas diffusion electrode substrate are suitable for use in fuel cells.

[0113] <Transportation>

[0114] The present invention relates to vehicles, such as automobiles, airplanes, or ships, that use the electrochemical device as a power source. Among these, fuel cells, as one type of electrochemical device, and solid polymer fuel cells are suitable as power sources for vehicles such as automobiles, airplanes, or ships.

[0115] Example

[0116] The present invention will be specifically described below through embodiments, but the present invention is not limited to these embodiments.

[0117] <Evaluation>

[0118] (1) Mass per unit area

[0119] For carbon fiber substrates, untreated conductive porous substrates, and hydrophobically treated conductive porous substrates (hereinafter collectively referred to as "substrate"), three 10cm × 10cm test pieces were collected from the substrates to be tested. The mass of the test pieces was measured, and the mass per unit area of ​​each test piece was calculated using the following formula.

[0120] Mass per unit area (g / m²) 2 = Mass of the test piece (g) / Area of ​​the test piece (m²) 2 )

[0121] The arithmetic mean of the mass per unit area of ​​the three test pieces (g / m²) 2The value obtained by rounding to the nearest whole number is used as the unit area weight of the substrate.

[0122] (2) Slip angle

[0123] A conductive porous substrate was placed horizontally, and a droplet of 10 μL of purified water was placed on it. The angle at which the droplet began to roll was measured using an automatic contact angle meter (DM-501 manufactured by Kyowa Interface Science Co., Ltd.). Ten measurements were performed at different locations on the conductive porous substrate, and the average value was taken as the slip angle.

[0124] (3) Mass ratio F / C

[0125] For areas observed using a scanning electron microscope (SEM) at 2000x magnification (Hitachi, Ltd. S-5500), energy dispersive X-ray diffraction (EDX) was employed. Electron beams were irradiated with an accelerating voltage of 20 kV, and the reflected characteristic X-rays were detected. The mass fractions of fluorine and carbon were quantified to derive the values, and the ratio of the fluorine mass fraction to the carbon mass fraction was calculated. This measurement and calculation was performed 10 times at randomly selected locations. From the 10 calculated ratios, the two highest and two lowest values ​​(a total of 4 values) were removed, and the average of the remaining 6 values ​​was calculated as the mass ratio F / C.

[0126] [Example 1]

[0127] (Carbon fiber substrate)

[0128] The material is cut into squares with sides of 10cm, a thickness of 190μm, and a unit area weight of 84g / m². 2 Carbon paper (TGP-H-060 manufactured by Toray Industries, Inc.) is used as the carbon fiber substrate.

[0129] (Resin loading process)

[0130] Add 3g of acetylene black (DENKA BLACK Li-100, a registered trademark of DENKA Corporation) as a nano-carbon coagulant, 7g of nonionic dispersant, and 3g of aqueous dispersion of polyethylene resin (Vylonal MD-2000, a registered trademark of Toyobo MC Corporation) to 200g of pure water. Stir the mixture using a mixer (Thinky ARE-310) at 2000rpm for 5 minutes to obtain a dispersion of nano-carbon and resin.

[0131] After impregnating the carbon fiber substrate in the obtained dispersion, it was dried at 100°C for 2 minutes.

[0132] (Heating process)

[0133] Then, it is heated at 320°C for 10 minutes to obtain a conductive porous substrate without hydrophobic treatment.

[0134] (Hydrophobic agent adhesion process)

[0135] Add 5g of a hydrophobic agent (Meishield (registered trademark) Z-210 manufactured by Meisei Chemical Industry Co., Ltd.) with non-fluorinated alkyl groups and no fluorine to 95g of pure water to prepare a hydrophobic treatment solution. Immerse the above-mentioned untreated conductive porous substrate in the solution, remove it, dry it at 100°C for 1 minute, and then dry it at 180°C for 10 minutes to obtain the hydrophobic treated conductive porous substrate.

[0136] The evaluation results are shown in Table 1. Although no fluoropolymer-based hydrophobic agent was used, it exhibited the same degree of hydrophobicity as conductive porous substrates that used fluoropolymer-based hydrophobic agents.

[0137] [Example 2]

[0138] In the resin loading process, the amount of acetylene black added was changed to 6g, the amount of nonionic dispersant added was changed to 14g, and the amount of aqueous dispersion of polyethylene resin added was changed to 6g. Otherwise, conductive porous substrates before and after hydrophobic treatment were obtained in the same manner as in Example 1.

[0139] The evaluation results are shown in Table 1. Although no fluoropolymer-based hydrophobic agent was used, it exhibited the same degree of hydrophobicity as conductive porous substrates that used fluoropolymer-based hydrophobic agents.

[0140] [Example 3]

[0141] Carbon nanotubes (MWCNT, LB220-84 manufactured by Cnano Corporation) were used as nano-carbon aggregates in the resin loading process. Otherwise, the same conductive porous substrate before and after hydrophobic treatment was obtained as in Example 1.

[0142] The evaluation results are shown in Table 1. Even when carbon nanotubes are used, similar to the case where carbon black is used, the conductive porous substrate exhibits the same degree of hydrophobicity as the substrate using fluoropolymer hydrophobic agents, despite the absence of fluoropolymer hydrophobic agents.

[0143] [Comparative Example 1]

[0144] (Carbon fiber substrate)

[0145] The same carbon fiber substrate used in Example 1 was employed.

[0146] (Resin loading process)

[0147] In Comparative Example 1, no resin loading process was performed.

[0148] (Hydrophobic agent adhesion process)

[0149] The above-mentioned carbon fiber substrate was immersed in a hydrophobic treatment solution, and otherwise, a hydrophobic conductive porous substrate was obtained in the same manner as in Example 1.

[0150] The evaluation results are shown in Table 1. The same level of hydrophobicity as the conductive porous substrate using fluoropolymer-based hydrophobic agents was not obtained.

[0151] [Comparative Example 2]

[0152] (Carbon fiber substrate)

[0153] The same carbon fiber substrate used in Example 1 was employed.

[0154] (Resin loading process)

[0155] In Comparative Example 2, no resin loading process was performed.

[0156] (Hydrophobic agent adhesion process)

[0157] Add 5g of tetrafluoroethylene-hexafluoropropylene copolymer (FEP) aqueous dispersion as a fluoropolymer hydrophobic agent to 95g of pure water to prepare a hydrophobic treatment solution. After impregnating the above carbon fiber substrate, dry it at 100°C for 1 minute.

[0158] (Heating process)

[0159] Then, it is fired at 400°C for 30 minutes to obtain a hydrophobic conductive porous substrate.

[0160] The evaluation results are shown in Table 1.

[0161] [Comparative Example 3]

[0162] (Carbon fiber substrate, resin loading process and heating process)

[0163] Using the same carbon fiber substrate as in Example 1, and undergoing the same resin loading and heating processes as in Example 1, a conductive porous substrate without hydrophobic treatment was obtained.

[0164] (Hydrophobic agent adhesion process)

[0165] Add 6g of tetrafluoroethylene-hexafluoropropylene copolymer (FEP) as a fluoropolymer hydrophobic agent to 94g of pure water to prepare a hydrophobic treatment solution. After immersing the untreated conductive porous substrate in the solution, remove it and dry it at 100°C for 1 minute.

[0166] (Heating process)

[0167] Then, by firing at 400°C for 30 minutes, a hydrophobic conductive porous substrate is obtained.

[0168] The evaluation results are shown in Table 1. In the conductive porous substrate containing a hydrophobic agent with fluorine atoms, the comparative example in which a resin containing nano-carbon aggregates is supported on carbon fibers showed a decrease in slip angle of 8° compared to Comparative Example 2, which did not support the resin.

[0169] On the other hand, in Example 1, where a resin containing nano-carbon aggregates was supported on carbon fibers in a conductive porous substrate containing a hydrophobic agent without fluorine atoms, the slip angle was reduced by 60° compared to Comparative Example 1, which did not support a resin containing nano-carbon aggregates. This demonstrates that the effect of the nano-carbon aggregates in this invention on improving hydrophobicity is significant when using a hydrophobic agent without fluorine atoms.

[0170] [Comparative Example 4]

[0171] The acetylene black in the resin loading process was replaced with graphite particles (average particle size 5 μm, manufactured by Chu-Chu graphite industry, flake graphite BF-5A), otherwise, the same conductive porous substrate before and after hydrophobic treatment was obtained as in Example 1.

[0172] The evaluation results are shown in Table 1. In this comparative example, the resin containing graphite particles supported on a carbon fiber substrate showed a 22° reduction in the slip angle compared to Comparative Example 1, which did not contain graphite particles. The slip angle was 61°, but this was insufficient to improve hydrophobicity to a level that could suppress flooding when used in fuel cells. Therefore, it is evident that the effect of the resin supported on carbon fibers in this invention on improving hydrophobicity is significant when using nano-carbon aggregates.

[0173] Table 1

[0174]

[0175] Industry availability

[0176] The conductive porous substrate of the present invention can be used as a gas diffusion electrode substrate or a constituent element of a gas diffusion electrode substrate in electrochemical devices such as solid polymer fuel cells.

Claims

1. A conductive porous substrate comprising carbon fibers, wherein a resin comprising nano-carbon aggregates is supported on the carbon fibers, the conductive porous substrate having a slip angle of 2° or more and 60° or less, and the mass ratio of fluorine content to carbon content (F / C) being 0.01 or less.

2. The conductive porous substrate according to claim 1 further comprises a hydrophobic agent.

3. The conductive porous substrate according to claim 1 or 2, wherein the primary particles of the nano-carbon aggregate are spherical.

4. The conductive porous substrate according to claim 1 or 2, wherein the primary particles of the nano-carbon aggregate have a particle size of 10 nm or more and 200 nm or less.

5. The conductive porous substrate according to claim 1 or 2, wherein the nano-carbon aggregate is composed of carbon black.

6. The conductive porous substrate according to claim 1 or 2, wherein the nano-carbon aggregate is a fibrous nano-carbon aggregate with a diameter of 5 nm or more and 200 nm or less.

7. The conductive porous substrate according to claim 1 or 2, wherein the proportion of the nano-carbon aggregate in 100% by mass of the conductive porous substrate is 0.5% by mass or more and 16.0% by mass or less.

8. The conductive porous substrate according to claim 2, wherein the hydrophobic agent has a non-fluorinated alkyl group.

9. The conductive porous substrate according to claim 8, wherein the number of carbon atoms constituting the non-fluorinated alkyl group is 8 or more and 40 or less.

10. The conductive porous substrate according to claim 2, when heat-treated at 400°C for 1 hour in an atmospheric atmosphere, exhibits a slip angle that increases by more than 10° or loses its hydrophobicity.

11. A gas diffusion electrode substrate having a porous layer containing carbonaceous particles and a binder resin on one side of the conductive porous substrate of claim 1.

12. The gas diffusion electrode substrate according to claim 11, wherein the mass ratio of fluorine content to carbon content in the porous layer (F / C) is 0.01 or less.

13. An electrochemical device comprising the conductive porous substrate of claim 1 or the gas diffusion electrode substrate of claim 11.

14. A means of transportation that uses the electrochemical device of claim 13 as a power source.

Citation Information

Patent Citations

  • Gas diffusion electrode substrate

    WO2015125750A1